Vascularization of a Bone Organoid Using Dental Pulp Stem Cells - Aonan Li; Jun-Ichi Sasaki; Gabriela L. Abe; Chihiro Katata; Hirohiko Sakai; Satoshi Imazato (Hindawi Limited, 2023)
Bone organoids offer a novel path for the reconstruction and repair of bone defects. We previously fabricated scaffold-free bone organoids using cell constructs comprising only bone marrow-derived mesenchymal stem cells (BMSCs). However, the cells in the millimetre-scale constructs were likely to undergo necrosis because of difficult oxygen diffusion and nutrient delivery. Dental pulp stem cells (DPSCs) are capable of differentiating into vascular endothelial lineages and have great vasculogenic potential under endothelial induction. Therefore, we hypothesized that DPSCs can serve as a vascular source to improve the survival of the BMSCs within the bone organoid. In this study, the DPSCs had greater sprouting ability, and the proangiogenic marker expressions were significantly greater than those of BMSCs. DPSCs were incorporated into the BMSC constructs at various ratios (5%-20%), and their internal structures and vasculogenic and osteogenic characteristics were investigated after endothelial differentiation. As a result, the DPSCs are differentiated into the CD31-positive endothelial lineage in the cell constructs. The incorporation of DPSCs significantly suppressed cell necrosis and improved the viability of the cell constructs. In addition, lumen-like structures were visualized by fluorescently labelled nanoparticles in the DPSC-incorporated cell constructs. The vascularized BMSC constructs were successfully fabricated using the vasculogenic ability of the DPSCs. Next, osteogenic induction was initiated in the vascularized BMSC/DPSC constructs. Compared with only BMSCs, constructs with DPSCs had increased mineralized deposition and a hollow structure. Overall, this study demonstrated that vascularized scaffold-free bone organoids were successfully fabricated by incorporating DPSCs into BMSC constructs, and the biomimetic biomaterial is promising for bone regenerative medicine and drug development.